2001
DOI: 10.1007/s001140100248
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic compass orientation of European robins under 565 nm green light

Abstract: European robins tested under monochromatic green light with a peak wavelength of 565 nm at an intensity of 2.1 mW m-2 in the local geomagnetic field preferred their migratory direction, heading southward in autumn and northward in spring. Inverting of the vertical component of the magnetic field caused the robins to reverse their headings, indicating that the birds used a magnetic inclination compass to locate their migratory direction. The behavior recorded under green light at an intensity of 2.1 mW m-2 is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…The activation in Cluster N under red light seemed to be slightly lower than under white light, but this difference was not significant. Initially, red light was shown to temporarily disrupt or lead to inappropriately aligned magnetic orientation under certain conditions (Wiltschko et al, 1993(Wiltschko et al, , 2001Wiltschko & Wiltschko, 1999, 2001bMuheim et al, 2002). However, recently Wiltschko et al (2004a) subsequently showed that when European robins are pre-exposed to the red light for ~1 h, the birds seem to regain their orientation capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The activation in Cluster N under red light seemed to be slightly lower than under white light, but this difference was not significant. Initially, red light was shown to temporarily disrupt or lead to inappropriately aligned magnetic orientation under certain conditions (Wiltschko et al, 1993(Wiltschko et al, , 2001Wiltschko & Wiltschko, 1999, 2001bMuheim et al, 2002). However, recently Wiltschko et al (2004a) subsequently showed that when European robins are pre-exposed to the red light for ~1 h, the birds seem to regain their orientation capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The test cages were lit with 565 nm green light at an intensity of 1.9 mW m 22 -birds have always shown excellent orientation using their inclination compass in this condition [18,21]. The activity was recorded for 60 min.…”
Section: (C) Test Proceduresmentioning
confidence: 99%
“…Although the results of many behavioural experiments suggested that the bird's compass actually worked on radical-pair reactions (for example, its sensitivity to the spectrum of the ambient light [20]), the crucial evidence was lacking. The situation has apparently changed with the demonstration of the effect of weak oscillating magnetic fields (OMFs) on the orientation ability of European robins (Erithacus rubecula) by the group of R. and W. Wiltschko in Frankfurt [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%